Optimal control problems with nonsmooth mixed constraints - De Pinho, M. D R; Silva, Geraldo Nunes [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In this paper we present a weak maximum principle for optimal control problems involving mixed constraints and pointwise set control constraints. Notably such result holds for problems with possibly nonsmooth mixed constraints. Although the setback of such result resides on a convexity assumption on the extended velocity set, we show that if the number of mixed constraints is one, such convexity assumption may be removed when an interiority assumption holds. © 2008 IEEE.
Keywords: Control constraints; Maximum principle for optimal controls; Mixed constraints; Non smoothes; Optimal control problems